The Operation and Regulation of Crude Oil and Gasoline Pipe Lines - Prewitt, Roy A. (Quarterly Journal of Economics, 1942)
Introduction, 177. — The importance of oil pipe lines, 178. — Concentration of control, 180. — Use of pipe lines by independent shippers, 182. — Minimum tender requirements, 184. — Storage facilities, 185. — Effects of shipping requirements, 186. — Rates and transportation costs, 189. — Effect of the rate and cost structure, 192. — Earnings, 193. — Subsidizing losses elsewhere, 199. — Regulation by the Interstate Commerce Commission: the Hepburn Act, 201; handicaps under which the Commission has operated, 204; Brundred Brothers vs. Prairie Pipe Line, 205; the Reduced Pipe Line Rates and Gathering Charges Investigation, 206.